Benefits and barriers to pediatric tele-urology during the COVID-19 pandemic - Winkelman, Andrew J. (J Pediatr Urol, 2020)
INTRODUCTION: Telemedicine video visits are an under-utilized form of delivering health care. However due to the COVID-19 pandemic, practices are rapidly adapting telemedicine for patient care. We describe our experience in rapidly introducing video visits in a tertiary academic pediatric urology practice, serving primarily rural patients during the COVID-19 pandemic. OBJECTIVE: The primary aim of this study was to assess visit success rate and identify barriers to completing video visits. The secondary aim identified types of pathologies feasible for video visits and travel time saved. We hypothesize socioeconomic status is a predictor of a successful visit. MATERIALS AND METHODS: Data was prospectively collected and analyzed on video visits focusing on visit success, defined by satisfactory completion of the visit as assessed by the provider. Other variables collected included duration, video platform and technical problems. Retrospective data was collected via chart review and analyzed including demographics, insurance, and distance to care. Socioeconomic status was estimated using the Distressed Communities Index generated for patient zip code. RESULTS/DISCUSSION: Out of 116 attempted visits, 81% were successful. The top two reasons for failure were “no-show” (64%) and inability to connect (14%). Success versus failure of visit was similar for patient age (p = 0.23), sex (p = 0.42), type of visit (initial vs. established) (p = 0.51), and socioeconomic status (p = 0.39). After adjusting for race, socioeconomic status, and type of provider, having public insurance remained a significant predictor of failure (p = 0.017). Successful visits were conducted on multiple common pediatric urologic problems (excluding visits requiring palpation on exam), and video was sufficient for physical exams in most cases (Summary Table). A median of 2.25 h of travel time was saved. CONCLUSIONS: While socioeconomic status, estimated using the Distressed Communities Index, did not predict success of video visits, patients with public insurance were more likely to have a failed video visit. There is compelling evidence that effective video visits for certain pathologies can be rapidly achieved in a pediatric urology practice with minimal preparation time.